Approaches to medical educational research - Judy McKimm (British Journal of Hospital Medicine, 2010, 2010)
Clinical teachers need to be able to make informed judgements about the quality of published educational research before drawing upon it to enhance their teaching and learning. Those wishing to conduct educational research may have to re-think the nature of 'evidence' to develop and use appropriate research approaches.